Cloning the human lysozyme cDNA: inverted Alu repeat in the mRNA and in situ hybridization for macrophages and Paneth cells. - Chung, L; Keshav, S; Gordon, S (1988)
Lysozyme is a major secretory product of human and rodent macrophages and a useful marker for myelomonocytic cells. Based on the known human lysozyme amino acid sequence, oligonucleotides were synthesized and used as probes to screen a phorbol 12-myristate 13-acetate-treated U937 cDNA library. A full-length human lysozyme cDNA clone, pHL-2, was obtained and characterized. Sequence analysis shows that human lysozyme, like chicken lysozyme, has an 18-amino-acid-long signal peptide, but unlike the chicken lysozyme cDNA, the human lysozyme cDNA has a greater than 1-kilobase-long 3' nontranslated sequence. Interestingly, within this 3' region, an inverted repeat of the Alu family of repetitive sequences was discovered. In RNA blot analyses, DNA probes prepared from pHL-2 can be used to detect lysozyme mRNA not only from human but also from mouse and rat. Moreover, by in situ hybridization, complementary RNA transcripts have been used as probes to detect lysozyme mRNA in mouse macrophages and Paneth cells. This human lysozyme cDNA clone is therefore likely to be a useful molecular probe for studying macrophage distribution and gene expression.